Message - Salvador-Tayag, Felicia Racquel (Philippine Journal of Allergy, Asthma and Immunology, 2022)
It is with great honor and privilege to lead the PSAAI@50 Golden Anniversary celebration. Looking back, I have always been inspired by my mentors during my fellowship training in Allergy and Immunology in the UP-PGH and the great and accomplished leaders of PSAAI. From 11 inspiring founders, we are now 154 strong, all over the archipelago and abroad! This is a time to look back, reminisce, reflect, and take pride in the accomplishments of PSAAI in the past 5 decades. Since its foundation in 1972, PSAAI has been recognized in the field of allergy and immunology not only locally but we have made our mark internationally as well through the efforts of our dedicated and passionate leaders and hardworking and committed members. We continue to excel in education, research, and community service. Through the society's activities, we serve not just our patients and colleagues but also the environment through our advocacies. This is a time to look ahead. This pandemic continues to bring challenges to the society but we rose and excelled to the occasion. PSAAI came to the forefront in the fight to end this pandemic. In this age of misinformation and fake news, PSAAI came up with well-researched, science-based position statements and guidelines in vaccination and treatment of COVID-19. Our members are also giving their time and talent in the national and regional government agencies as advisers and experts in vaccination, allergy, and immunology. These are the society's services to the Filipino people. This year, we celebrate PSAAI's 50 glorious years, and we will continue to make history in the next 50 years and beyond. This book compiles the achievements and wonderful memories of PSAAI in the past 5 decades. May this inspire the young and future members to continue the legacy of what our elders started and continue to excel beyond what is expected. We praise and thank God for continuously guiding us in all our endeavors and may He continue to strengthen our camaraderie and lead us to pursue our commitment to excellence and service. Congratulations, PSAAI! I am proud to be PSAAI!